Pengaruh Media Game Educandy Terhadap Pengetahuan Hipertensi Pada Remaja di Desa Telaga Murni - Rifka Syifa Zakiya; Ratih Kurniasari (Program Studi Gizi UNSIKA, 2021)
Background: knowledge of hypertension in adolescents. Education is one way that can be used to increase one's knowledge. Educational games are games designed to increase one's knowledge. Educandy is a web-based game application that can be used as a medium for learning. The educational games used are multiple choice. Objective: The study was conducted to determine the effect of using game media on knowledge of Hypertension in Adolescents. Methods: pre-experimental design research with one group pretest-posttest design. The number of samples was determined by purposive sampling as many as 18 teenagers aged 18-24 years in Telaga Murni Village. Results: the results of this study indicate that there is an increase in knowledge from 12.78 to 14.28. Based on statistical tests using the Wilcoxon test, it was proven that there was an increase in the average score of knowledge before and after being given nutrition education with the